Hubungan BCS dengan Produksi dan Total Solid (TS) Kolostrum Sapi PFH di KPSP Setia Kawan Pasuruan - Luluk Puji Mandharenie; Puguh Surjowardojo (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2022)
The study was carried out at the Setia Kawan Nongkojajar Dairy Farm Cooperative for 3 months on August 24 – October 24, 2021. The purpose of this study was to determine the relationship between BCS of dairy cows with the quantity and quality of colostrum in terms of Total Solid (TS) colostrum. The material used in this study was 42 Friesian Holstein crossbred dairy cattle (9 months). The standard for measuring BCS is the standard from Kellogg (2010). The variables used were the BCS value, the quantity of colostrum production and the Total Solid (TS) of colostrum in dairy cows. The method used is a case study method and the determination of crossbred dairy cattle material using purposive sampling. The data were analyzed by simple linear regression with the BCS of dairy cattle, namely (????), colostrum production is (????1) and TS namely (????2). The results of the study obtained the equation ????1 = 3.62 + 0.14X relationship between BCS and colostrum production and the equation ????2 = 18.25 + 3.69X between the relationship between BCS and TS, the equation is used as a basis for estimating the quality of colostrum in terms of TS with (r) = 0.50 and ????2 = 0.2509% while the quantity of colostrum in terms of daily colostrum production with (r) = 0.043 and ????2 = 0.0018%. From these calculations, it can be seen that BCS is significantly related (p<0.05) on the TS of colostrum and has a positive relationship, while BCS was not significantly related (p>0.05) on the quantity of colostrum production.